Cotidianeidad de la enfermera en proceso de cuidar cuidado en el primer nivel de atención - Aredo Hilario, Kathia Felicita (2016)
This qualitative research approach Dialectical was held in the Province of Otuzco in the Health Center Ramón Castilla belonging to Otuzco Health Network. It was aimed to describe the daily lives experiencing the nurse to provide its Caring / Care and analyze the dimensions of everyday nurse in the process of care / care at the primary care level in the Health Center Ramón Castilla. Participants were 7 nurses (as). The scenario study was the Health Center Ramón Castilla. The speeches were collected through semi-structured interviews. The analysis of the speeches, originated three categories: 1) "Daily CARE WITH precautionary approach" with sub category: Care vs. Care in the first level of care. 2) CARE "NOT EVERYDAY WITH PROMOTIONAL approach with sub category: Nursing care at the first level of care, emotional care, Care and Care as communication and education. 3) CONCEPTION ACTION VS "with sub category: Conceptions of nursing care and nursing ambivalent feelings.